Desenvolvimento de produto seco por aspersão obtido a partir das amêndoas de Bertholletia excelsa H.B.K - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The plant species Bertholletia excelsa HBK popularly known as “castanha-do-Brazil” is widely used by popular cuisine of the Amazon due to its pleasant taste and its nutritional value. Among its main chemical constituents stand out selenium. Pharmacological studies with almonds this species showed antioxidant activities. To facilitate the integration of castanha- do- Brazil in the brazilian diet is necessary to establish technological improvements. This paper refers to the development and technological characterization of granular materials by spraying from aqueous extraction solution of Bertholletia excelsa HBK almonds. The plant material of Bertholletia excelsa HBK was collected in different Manaus processing plants and different vintages. The dried products were produced using a 22 factorial design type, having as independent variables the type of glidant (maltodextrin and gum arabic) and dependent variables technological and organoleptic characteristics of the obtained dry extract and the ratio of adjuvants used, as well as the chemical composition and analysis of the shelf life of products with higher yields. Among the technological parameters evaluated in the post stand out from the operating income, residual moisture and water activity. In addition, the antioxidant activity was evaluated and the selenium content of the products obtained. The results of this research allowed to observe that the studied parameters are within the limits recommended by the National Health Surveillance Agency. However, all other evaluated parameters showed statistically significant quantitative differences between samples studied suggesting that soil and climatic conditions alter the physical and chemical characteristics of this species and therefore may influence the quality, efficacy and safety of the final product proposed.
Keywords: Castanha- do- Brasil; Produto Seco por Aspersão (PSA); Brazil nuts; Classificação Botânica - Castanha-do-Brasil; Alimentos Funcionais; Composição Nutricional - Castanha-do-Brasil; CIÊNCIAS DA SAÚDE: FARMÁCIA